PENINGKATAN PENDAPATAN RUMAH TANGGA PETANI DENGANTANAMAN PEKARANGAN “KUJARAI” DI LUBUK PANDAN - Syamsuwirman; Yonny Arita Taher; Herda Gusvita (Ekasakti Jurnal Penelitian dan Pengabdian, 2020)
Nagari Lubuk Pandanis an agricultural area tha has the potential for hay. This potential hasnot been exploited by farmers, even though hay can provide nutrients and soil organic matter.The farmers’ problem is the lack of access to production facilities such as in-organicfertilizers. Based on this problem, there has been activity that help farmers produce organicfertilizers and apply it to their home gardens, which can increase their income. The aim of theactivity in general is to increase farmers' income by producing organic fertilizers used for“kujarai” crops (turmeric, ginger, lemongrass). The activity is planned to be carried out byKKN students after the proposal is accepted by the Ministry of Research and Technology,dated January 28, 2020. However, due to the Covid-19 pandemic that occurred in 2020, thereis a ban on gathering which also has an impact on changing the KKN system. Therefore,students carry out activities around their home or origin. Furthermor, the activity wasexpanded from Nagari Lubuk Pandan to Padang Pariaman District. The technicalimplementation, first, record data on students who live in Padang Pariaman Regency, with 30students who carry out the activity. Each student fostered and planted "Kujarai" in the yard of10 families. From the activities that have been carried out, it is estimated that each farmerwill get an increase in income in the next 6-7 month. The target for this activity is thatfarmers are able to make organic fertilizer from agricultural waste and apply it to crops,maximizingtheir yards to increase community income.